Eda edilmeyen namazların telafisi - Saraç, Şule (My University, 2010)
Namazların Telafisi, İbadet ÖZET EDA EDİLMEYEN NAMAZLARIN TELAFİSİ İbadetler İslam dininin temel unsurlarındandır. Her ibadetin kendine has kuralları vardır. Önemli bir ibadet olan namaz hakkında bilinmesi gereken pek çok husus bulunmaktadır. Bunlardan birisi de namazın dince belirlenmiş olan vakti içinde ifa edilmesidir. Herhangi bir sebepten dolayı bu görev vaktinde yerine getirilemediğinde bir telafisi olup olmadığı, şayet varsa bu telafilerin nasıl yapılacağı tezimizin konusunu oluşturmaktadır. Araştırmamız sonucunda kılınmayan namazın telafisinin kaza ve tövbe etmek şeklinde uygulandığı tespit edilmiştir. Ölünün namaz borçlarının telafisinde ise farklı yollara başvurulmuştur. Fidye vererek bu borçlardan kurtulmak bir çare olarak düşünülmüştür. Restitution of prayers, Worship

RESTİTUTİON OF PRAYERS THAT WERE NOT PERFORMED Worship is one of Islam's fundamental principals. Every different kind of worship has its own obligations. An important kind of worship is daily prayers. There are many particulars to be known about daily prayers. One of the particulars is that it has a specific time to be performed. Our thesis is based on the subject that whether it is possible to restitute for prayers that were not performed during the specified times and if it is possible what is the correct way of performing this restitution. The results of our research conclude that restitution for missed prayers are performed in the way of repentance and late performance of the prayer. But different ways have been instituted for the unperformed prayers of a deceased. In this case giving charity in lieu of the prayer has been thought to be a way for remedy.
Keywords: İbadet; İslam Dini; İslam Hukuku; Namaz